Comparison Between Cephalometric Measurements Derived from Cone Beam Computed Tomography and Lateral Cephalogram - Khan, Mehwish; Khan, Azhar Bangash; Amin, Erum; Ejaz, Fatima; Tariq, Sana; Akhtar, Faheem Nake (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the mean craniofacial linear and angular measurements derived from cone beam computed tomography synthesized lateral cephalogram and those obtained from conventional cephalogram. Study Design: Comparative cross-sectional study. Place and Duration of Study: Armed Forces Institute of Dentistry (AFID), Rawalpindi Pakistan, from Feb 2017 to Nov 2018. Methodology: Sample size was 32. Following linear measurements were evaluated; anterior facial height, right side and left side of mandibular length, nasal spine length, Upper and lower incisors to A-Pog distance. These measurements were obtained by both means i.e., conventional cephalogram and cone beam computed tomography synthesized cephalogram. Each of the measurement were taken twice by the single operator with a difference of two weeks. Results: No significant difference was found among measurements obtained through lateral head film cephalograph and cone beam synthesized cephalograph except for mandibular length (for which p=0.04). Conclusions: Cone beam computed tomography synthesized lateral cephalogram can be suggested as a substitute to conventional lateral cephalogram. Especially in conditions when cone beam computed tomography is already required for treatment planning thus reducing supplementary x- ray exposure and expenditure of an additional x-ray.